From squid giant axon to automated patch-clamp: electrophysiology in venom and antivenom research - Ahmadi, Shirin; Benard-Valle, Melisa; Boddum, Kim; Cardoso, Fernanda C.; King, Glenn F.; Laustsen, Andreas Hougaard; Ljungars, Anne (Frontiers in Pharmacology, 2023)
Ion channels play a crucial role in various physiological processes, including neurotransmission and muscle contraction. Venomous creatures exploit the vital function of ion channels by producing toxins in their venoms that specifically target these ion channels to facilitate prey subduction and capture upon a bite or a sting. Envenoming can therefore lead to ion channel dysregulation, which for humans can result in severe medical complications that often necessitate interventions such as antivenom administration. Conversely, the discovery of highly potent and selective venom toxins with the capability of distinguishing between different isoforms and subtypes of ion channels has led to the development of beneficial therapeutics that are now in the clinic. This review encompasses the historical evolution of electrophysiology and patch-clamp methodologies, highlighting their contributions to venom and antivenom research, including venom-based drug discovery and evaluation of antivenom efficacy. By discussing the applications and advancements in patch-clamp techniques, this review underscores the profound impact of electrophysiology in unravelling the intricate interplay between ion channels and venom toxins, ultimately leading to the development of drugs for envenoming and ion channel-related pathologies.